Naturaleza y cultura: una lectura elemental de Arráncame la vida de Ángeles Mastretta - Bodevin, Leon (2004)
This article states that Mastretta's Arráncame la vida reinforces Simone de Beauvoirs conception of the woman as an individual that has the right to live according to her own individuality and nature. In addition, emphasizes Camille Paglia's notion that sex is the point of contact between man and nature. In Arráncame la vida, the protagonist consciously ignores the order that the culture inflicts on her. She is truthful and loyal to her conciousness. Therefore. the protagonist needs to materialize her own revolution in order to be loyal to her individuality. Supportive to her effort, nature itself, personified by the woman from Atincingo. assists Catalina's pursuit. So, Catalina recovers the freedom to be honest and loyal to herself.